مفهوم مصطلح الجملة قديماً وحديثاً - القضماني رضوان; عبد القادر ميساء (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
كَثُرت التحديدات التعريفية الخاصة بالجملة منذ الدراسات اللغوية الإغريقية حتى أيامنا هذه. وقد انصبّت جميعها في محورين مدارهما: علاقات الإسناد، وإفادة دلالة معيّنة. يتفرّع على المحور الأول مجموعة الضوابط النحوية الخاصّة بكل لغة. ويقوم عليها وعلى الدلالة مبدأ قبول جملةٍ بعينها، مع ما يتّخذه مبدأ القبول هذا من درجات متباينة بين حدّ أعلى في القبول وحدّ أدنى، وبينهما درجات أُخرَ. وإذ أسهم اللغويون العرب القدماء برصيد مهم في هذا المجال، فقد برّز فيه الغربيّون من المحدثين أيضاً. وجاءت نتائج دراساتهم متّفقةً،في كثير من الأحيان، مع ما سبق للعرب الغوص فيه، وإن يؤثر لهم تميّزهم بالعلمية والمنهجية والشمولية. يهدف هذا البحث إلى استجلاء مفهوم الجملة عند اللغويين العرب القدماء، واستجلاء أحكامهم التي قامت عليها مسألة قبول هذه الجملة من دون تلك، مع تبيان ما أفرزته أبرز الدراسات اللغوية الحديثة عند الغربيين بهذا الشأن، تأكيداً منا أنّ الفكر الإنساني واحد، وإن اختلفت الأزمنة، وتباينت الطرق المتبعة. All numerous sentence related definitions, starting from Greek linguistic studies up to present ones have revolved around two axes: ascription and reporting of specific indications. The first axis is branched off into groups of grammatical limitations related to each language, on which and an indication of the acceptance of a sentence is made, together with what comes with this rule of variable degrees ranging between max-acceptance and min-one plus others in between. Ancient Arab linguists contributed a lot to this field in which western modernists are also remarkable, their study results are in consistency most often with what Arabs had already addressed, although westerns were distinguished in scientific, methodological and comprehensive aspects. This paper tries to clarify ancient Arab linguist’s concept of sentence, explain the principle upon which they depended in their acceptance or rejection of a particular sentence, and highlight new western studies in this field. This is to emphasize shared human thinking despite differences of times and methods.